Identification of RAGE and OSM as New Prognosis Biomarkers of Severe Pneumonia - Jing Lei; Li Wang; Qian Li; Lin Gao; Jing Zhang; Yan Tan (Canadian Respiratory Journal)
Objective. To investigate efficiency of RAGE and OSM as new prognosis biomarkers of severe pneumonia. Methods. Eligible patients were classified into hypoxemia and nonhypoxemia groups. Meanwhile, the same cohort was divided into survival and nonsurvival groups after a post-hospital stay of 30 days. We analyzed risk factors for the hypoxia and death among these patients. Results. Compared with nonsurvival group, significant increase was noticed in PH, lymphocyte, albumin and platelet level in survival group, while significant decline was noticed in neutrophils, RBC, hemoglobin, hematocrit, creatinine, total bilirubin, CRP, PCT, OSM, RAGE and neutrophils/lymphocyte level. Oxygenation index level was related to APACHE II, LIS, SOFA, NUTRIC score, WBC, neutrophils, lymphocyte, RAGE, and albumin level (p<0.05). LIS, SOFA, NUTRIC score, lac, lymphocyte, platelet, BUN, total bilirubin, PCT, and OSM levels were associated with mortality rate (p<0.05). Conclusions. RAGE and OSM may serve as a new biomarker for poor prognosis in pneumonia patients.